2018
DOI: 10.1002/hon.2567
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles discriminate childhood T‐ from B‐acute lymphoblastic leukemia

Abstract: MicroRNAs (miRNAs) play a critical role on biological and cellular processes; the search for functional markers may be of importance for differential diagnosis, prognosis, and development of new therapeutic regimens. In this context, we evaluated the bone marrow miRNA profile of Brazilian children exhibiting T‐ or B‐cell acute lymphoblastic leukemia (T‐ALL or B‐ALL), using massive parallel sequencing, using the HiSeq 2500 platform (Illumina). The differential expression analysis was conducted considering a lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 75 publications
(113 reference statements)
0
44
0
Order By: Relevance
“…However, a machine learning analysis showed that miR-29c-5p, which is involved in calcium signaling, is critical for B-cell lymphocyte fate. So, it is the best discriminator between childhood T-and B-ALL [40].…”
Section: Mirna Expression and Its Role In The Differential Diagnosis mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a machine learning analysis showed that miR-29c-5p, which is involved in calcium signaling, is critical for B-cell lymphocyte fate. So, it is the best discriminator between childhood T-and B-ALL [40].…”
Section: Mirna Expression and Its Role In The Differential Diagnosis mentioning
confidence: 99%
“…A study in Brazilian children with T-or B-cell acute lymphoblastic leukemia (T-ALL or B-ALL) evaluated a bone marrow miRNAs profile that may be used for distinguishing childhood lymphoblastic leukemia subtypes [40]. The authors mention that miR-708-5p, miR-497-5p, miR-151a-5p, miR-151b, miR-371b-5p, miR-455-5p, miR-195-5p, miR-1266-5p, miR-574-5p, miR-425-5p downregulated and miR-450b-5p, miR-450a-5p, miR-542-5p, miR-424-5p, miR-629-5p, miR-29c-5p upregulated in childhood T-ALL may be used for distinguishing childhood T-and B-ALL subtypes.…”
Section: Mirna Expression and Its Role In The Differential Diagnosis mentioning
confidence: 99%
“…These micro markers have proven to be very promising chALL biomarkers and have widespread clinical applications because of their stability and resistance to degradation in not only blood, but also various biological specimens (such as tissue, sputum, stool and formalin-fixed paraffin-embedded (FFPE) specimens), easily measured, and most importantly, their quantities correlates with the presence of the malignancy or with clinically relevant malignancy features (8,14,(95)(96)(97). Recent studies have revealed that extracellular circulating miRNA levels in secreted membrane vesicles (microvesicles and exosomes), blood serum, and other body fluids can be used as biomarkers to diagnose, classify and predict prognosis of chALL (96,(98)(99)(100)(101). miRNA expression dysregulation in cancers is because of different mechanisms, such as deletion or amplification of miRNA related genes, abnormal transcriptional control of miRNAs, epigenetic dysregulation and defects in the biogenesis machinery of miRNA (102).…”
Section: Mirna Levels Alterationmentioning
confidence: 99%
“…Due to the promising characteristics of high stability, low cost, possibility of repeated sampling and noninvasiveness, circulating biomarkers have received extensive attention in molecular medicine nowadays. Compelling evidences have shown that these types of biomarkers are measurable in secreted membrane vesicles (microvesicles and exosomes), blood serum, and other body fluids and can be used as biomarkers to diagnose, classify, follow-up and predict prognosis in chALL (96,(98)(99)(100)(101). It has been suggested that extracellular circulating biomarkers play an important role in intracellular communication in both paracrine and endocrine manners (101).…”
Section: Circulating Biomarkersmentioning
confidence: 99%
“…MiR-146b could delay the aggressiveness and progression of T-ALL (29). miR-1266 was downregulated in childhood T-ALL and might be used to distinguish childhood ALL subtypes (30).…”
Section: Genome-wide Microrna Profiles Associated With Clic4 Expressionmentioning
confidence: 99%